Effect of thermally treated wood. Issue 1 (October 2020) - Gazizov, A; Popova, E; Ozden, I; Zairov, A
Abstract: There are many studies on the thermal treatment of wood, but the treatment of thermally modified wood with different flame retardants, and the changes that occur in this process are not fully understood. This paper assesses various thermal modifications and the flame retardant effect on thermally modified wood under conditions that simulate the natural process of wood combustion by a heat source, constant air flow and exhaust gas flow. The research temperature ranges from 160 to 260° C. It has been experimentally proven that thermally modified wood impregnated with a fire retardant has a greater fire and ignition resistance than untreated wood.